2004
DOI: 10.1007/s00253-004-1682-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of arachidonic acid production by mutants with lower n-3 desaturation activity derived from Mortierella alpina 1S-4

Abstract: Five mutants were obtained, Y11, Y135, Y164, Y180 and Y61, capable of accumulating higher amounts of arachidonic acid (AA) than Mortierella alpina 1S-4, an industrial strain for the production of AA-rich triacylglycerol (TG). This is thought to be due to low or no activity of n-3 desaturation with conversion of AA to eicosapentaenoic acid, which functions at a cultural temperature below 20 degrees C. In small-scale cultivation under optimum conditions, Y11 and Y61 respectively accumulated 4.97 mg/ml and 4.11 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…CSL gave the maximum biomass and ARA yield in the culture, which also has the lowest residual glucose content at the end of fermentation. A slightly lower biomass and ARA yield were obtained in the medium containing YE, which is a typical nitrogen source for the cultivation of microorganisms, owing to the presence of metal ions and required micronutrients vital for the growth of microorganisms (Lan et al 2002;Sakuradani et al 2004). It is also showed that a high ARA percentage, as a fraction of total lipids (approximately 46 %), could also be obtained in medium supplemented with either CSL or YE as the sole nitrogen source.…”
Section: Resultsmentioning
confidence: 75%
“…CSL gave the maximum biomass and ARA yield in the culture, which also has the lowest residual glucose content at the end of fermentation. A slightly lower biomass and ARA yield were obtained in the medium containing YE, which is a typical nitrogen source for the cultivation of microorganisms, owing to the presence of metal ions and required micronutrients vital for the growth of microorganisms (Lan et al 2002;Sakuradani et al 2004). It is also showed that a high ARA percentage, as a fraction of total lipids (approximately 46 %), could also be obtained in medium supplemented with either CSL or YE as the sole nitrogen source.…”
Section: Resultsmentioning
confidence: 75%
“…As a precursor of prostaglandins, thromboxane, prostacyclin, and leucotrienes, it owns various physiological functions [1,2] and has been found wide application in medicine, pharmacology, cosmetics, food industry, agriculture, and other fields [3]. Production of ARA by cultivation of Mortierella fungi, which are thought to be the most prominent ARA source [4], has been widely reported [5][6][7][8], focusing on the optimization of cell morphology, dissolved oxygen concentration, and medium compositions.…”
Section: Introductionmentioning
confidence: 99%
“…As a precursor of prostaglandins, thromboxane, prostacyclin, and leucotrienes, it has various physiological functions [1] and has been found to have wide applications in medicine, pharmacology, cosmetics, the food industry, agriculture, and other fields [2]. Production of ARA by cultivation of Mortierella fungi, which are thought to be the most prominent ARA source [3], has been widely reported [4]. Over the past 20 years, the effects of cell morphology and medium compositions, including carbon, nitrogen sources, and mineral addition, on ARA productivity have been widely investigated and known as the key factors.…”
Section: Introductionmentioning
confidence: 99%